[PP.13.13] FIBROMUSCULAR DYSPLASIA – THE REASON OF SEVERE RENOVASCULAR HYPERTENSION IN NEWBORN. (September 2017) - Antoniewicz, J.; Lesiak, J.; Brzezinska-Rajszys, G.; Kalicinski, P.; Grajkowska, W.; Pyzlak, M.; Kosciesza, A.; Grenda, R.
Abstract : Objective: INTRODUCTION: Fibromuscular dysplasia (FMD) is a non-atherosclerotic, non-inflammatory disease of the blood vessels that causes abnormal growth within the wall of an artery. The most common arteries affected are renal and carotid arteries. FMD predominantly affects middle-aged women, but has been found in men and people of all ages. Pediatric cases of FMD are vastly different from that of the adult population. Design and method: THE AIM of this report is to present a newborn girl with severe arterial hypertension (HT) caused by bilateral renal arterial stenosis due to FMD. Results: CASE REPORT: Newborn girl (23 days old) was admitted to the intensive care unit with respiratory insufficiency and arterial hypertension (120/89 mmHg). Coarctation of aorta was excluded (echocardiography). Abdomen ultrasound (US) with Doppler, 3D spiral computer tomography (CT) revealed critical stenosis of the left renal artery. The following renal scintigraphy showed lack of filtration in the left kidney. The patient received pharmacological treatment (amlodipine, propranolol) and was scheduled for a nephrectomy. Five months later, the operation was performed and the pathology assessment described 'FMD-like lesions' in the renal vessels. Due to gradual increase of blood pressure in the one month postoperative follow-up, US and angio-CT were carried out. Longitudinal stenosis of the right renal artery was confirmed and the child was qualified for the percutaneous transluminal angioplasty (PTA). During the procedure persistent irreversible spasm of the renal artery occurred and it resulted in emergency autotranplantation of the right kidney. Since there was no blood flow few hours postoperatively, the nephrectomy was necessary. The patient from then on been successfully treated with renal replacement therapy (firstly hemodialysis, then peritoneal dialysis). At the age of 15 months, the child does not need hypertensive pharmacotherapy and is qualified for kidney transplantation. Conclusions: 1. FMD in young children can be reason of severe renovascular hypertension. 2. Invasive treatment (PTA, surgery) in this cases is very difficult and risky.